2021
DOI: 10.2188/jea.je20200443
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality From Suicide During the Early COVID-19 Pandemic Period in Japan: A Time-Series Modeling Before the Pandemic

Abstract: Background Suicide amidst the coronavirus disease (COVID-19) pandemic is an important issue. In Japan, the number of suicides in April 2020 decreased by nearly 20% from that in 2019. To assess the impact of an infectious disease pandemic, excess mortality is often discussed. Our main purpose was evaluating excess mortality from suicide in Japan during the early pandemic period. Methods We used data on suicides collected by the National Police Agency of Japan until June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 26 publications
8
45
1
2
Order By: Relevance
“…1; Bernal, Cummins, & Gasparrini, 2017 , 2020 ; Bhaskaran, Gasparrini, Hajat, Smeeth, & Armstrong, 2013 ), a quasi-experimental study design (Shadish, Cook, & Campbell, 2002 ), widely used in COVID-19 suicide research (Leske et al, 2021 ; Pirkis et al, 2021 ), to compare monthly incident suicide attempt rates before and during the COVID-19 pandemic. Data collection covered the period from 1 January 2013 to 1 February 2021, thus included three waves of severe restrictions and extended existing studies of the first wave (Anzai, Fukui, Ito, Ito, & Takahashi, 2021 ; Calderon-Anyosa & Kaufman, 2021 ; Vandoros et al, 2020 ). The ITS study design used electronic health registry data that are continuously collected over time.…”
Section: Methodsmentioning
confidence: 99%
“…1; Bernal, Cummins, & Gasparrini, 2017 , 2020 ; Bhaskaran, Gasparrini, Hajat, Smeeth, & Armstrong, 2013 ), a quasi-experimental study design (Shadish, Cook, & Campbell, 2002 ), widely used in COVID-19 suicide research (Leske et al, 2021 ; Pirkis et al, 2021 ), to compare monthly incident suicide attempt rates before and during the COVID-19 pandemic. Data collection covered the period from 1 January 2013 to 1 February 2021, thus included three waves of severe restrictions and extended existing studies of the first wave (Anzai, Fukui, Ito, Ito, & Takahashi, 2021 ; Calderon-Anyosa & Kaufman, 2021 ; Vandoros et al, 2020 ). The ITS study design used electronic health registry data that are continuously collected over time.…”
Section: Methodsmentioning
confidence: 99%
“…Given the antecedents of observations in previous crises on their consequences for people's mental health and the increase in suicides [4][5][6][7][8][10][11][12], a similar impact could be expected during the course of the COVID-19 pandemic. Some studies have already shown the negative consequences of this crisis on mental health [2,3,[27][28][29], but there as yet seems to be no evidence for any increase in DBS during the confinement period-rather there seems to be stability [32][33][34] or a decline [35][36][37][38][39][40]-and there are still insufficient data to indicate otherwise. Nonetheless, the possible immediate impact in the months following confinement and the general medium and long term impacts remain to be explored in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, following the recommendations of the WHO [46], in order to implement preventive programs that stop or reduce such suicidal behaviors, as for example, the existing plans of prevention of Spain's various Autonomous Communities [47][48][49], it would be necessary to monitor the epidemiological trends of suicide in specific geographic areas through studies that help determine which population groups are at greatest risk, as some affected groups (such as women, adolescents, the elderly, or people with depression and post-traumatic stress disorder) suffer more and are more vulnerable to disasters [45]. The aforecited reference studies [32][33][34][35][36][37][38][39][40] respond implicitly to the need for this type of research at a local level, and their findings will be of relevance for the design of suicide prevention strategies in their specific zones of study. In this sense, a comparative analysis of the DBS registered by the IMLyCFs of Spain's various Autonomous Communities would show whether the results of this present study done at a local level are generalizable nationally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations